STUDI PUSTAKA PEMETAAN GEOLOGI DIGITAL (DIGITAL GEOLOGICAL MAPPING) BERBASIS SMARTPHONE - Rohaendi, Nendi; Herlinawati, Herlinawati; Setiawan, Iwan Fahlevi; Wahyudi, Wahyudi (PPSDM Geominerba, 2024)
Digital maps are representations of geographic phenomena stored for display and analysis by computers. A digital map can also be interpreted as a digitally presented image of the earth's surface that is reduced to a certain scale through a projection system. Digital geological mapping using smartphones is increasingly popular because it provides many conveniences. The purpose of this paper is to discuss which smartphone (smart phone) based operating system is the best in terms of accuracy for digital geological mapping. The market share of smartphones is currently controlled by three big players, namely Android, Windows and IOS. The results of a literature search show that there are two most popular operating systems for digital geological mapping, namely Android and IOS. Based on the review results, even though Android has the largest market share, iOS-based smartphones have various advantages in terms of reliability and accuracy.